Transformation of Principal’s Leadership in Building Teacher’s Motivation and Performance - Muhamad Sofiul Fuad; Tri Widayatsih; Mulyadi Mulyadi (Journal of Social Work and Science Education, 2027)
This study aims to: (1) describe the implementation of the four dimensions of the principal's transformational leadership (idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration) at SDN 10 Muara Sugihan; (2) analyze the principal's strategies in building and sustaining teacher work motivation through a transformational approach; and (3) explore the implications of these leadership practices on improving teachers' performance in the learning process. Employing a qualitative case study design, data were collected through in-depth interviews, participatory observation, and documentation from purposively selected informants, including the principal, five teachers, a school supervisor, and administrative staff. Analysis followed the interactive model of Miles, Huberman, and Saldaña, with validity ensured through triangulation and member checking. The principal demonstrated transformational leadership through concrete role modeling, contextual vision communication, and consistent appreciation of teacher performance. Motivation-building strategies included creating a humanistic organizational climate, strengthening teachers' sense of belonging, and employing emotionally supportive approaches. These practices tangibly improved teacher performance in lesson planning, teaching creativity, and professional discipline. This study uniquely positions work motivation as a key mediating mechanism linking transformational leadership to teacher performance in a rural Indonesian elementary context. Findings emphasize that principals must adopt humanizing, emotionally supportive approaches alongside structural strategies to sustain teacher motivation effectively. This research contributes empirical evidence that transformational leadership, when enacted through relational and motivational dimensions, significantly enhances teacher professionalism, offering actionable insights for school leaders in similar underserved settings.